TECHNIQUES FOR OVERCOMING THE FEAR OF DEATH ACCORDING TO BUDDHISM - Lauw Acep; Ida Bagus Gde Yudha Triguna; I Gusti Bagus Wirawan; Sutrisno (Vidyottama Sanatana: International Journal of Hindu Science and Religious Studies, 2025)
The fear of death is a fundamental existential issue that has been widely discussed in psychology, philosophy, and religious studies. This dissertation explores the phenomenon of death anxiety from the perspective of Buddhism, which offers a unique approach to understanding and overcoming the fear of death. Using a qualitative methodology, data was collected through in-depth interviews with 108 students from Nalanda Institute who study textual analysis of Buddhist scriptures, including the Sutta Pitaka, Abhidhamma, and Visuddhimagga. The research findings indicate that the fear of death in Buddhism is primarily rooted in attachment (tanha) and ignorance (avijja), which lead to suffering (dukkha). However, through practices such as mindfulness (sati), insight meditation (vipassana), and the cultivation of wisdom (panna), individuals can gain a deeper understanding of impermanence (anicca), thereby reducing their anxiety about death. Additionally, Buddhist concepts such as death, karma, and their implications in overcoming the fear of death play a crucial role in shaping attitudes toward mortality. This study contributes to a deeper understanding of meditation practices, the application of the Noble Eightfold Path found in the Sutta Pitaka, as well as an understanding of the nature of the mind as explained in the Abhidhamma and the path of purification (Visuddhimagga). With consistent practice, one can attain a state of inner peace in facing death.